Expanding Core-Collapse Supernova Search Horizon of Neutrino Detectors. (February 2020) - Halim, Odysse; Vigorito, C; Casentini, C; Pagliaroli, G; Drago, M; Fafone, V
Abstract: Core-Collapse Supernovae, failed supernovae and quark novae are expected to release an energy of few 10 53 ergs through MeV neutrinos and a network of detectors is operative to look online for these events. However, when the source distance increases and/or the average energy of emitted neutrinos decreases, the signal statistics drops and the identification of these low statistic astrophysical bursts could be challenging. In a standard search, neutrino detectors characterise the observed clusters of events with a parameter called multiplicity, i.e. the number of collected events in a fixed time-window. We discuss a new parameter called ξ (=multiplicity/duration of the cluster) in order to add the information on the temporal behaviour of the expected signal with respect to background. By adding this parameter to the multiplicity we optimise the search of astrophysical bursts and we increase their detection horizon. Moreover, the use of the ξ can be easily implemented in an online system and can apply also to a network of detectors like SNEWS. For these reasons this work is relevant in the multi-messengers era when fast alerts with high significance are mandatory.